2016
DOI: 10.1002/iid3.98
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a peptide‐based anti‐IgE conjugate vaccine in non‐human primates

Abstract: The anti‐human immunoglobulin E (IgE) monoclonal antibody, omalizumab (Xolair®, Genentech, South San Fransisco, CA), is effective in the treatment of poorly controlled moderate to severe allergic asthma and chronic idiopathic urticaria. It acts by specifically binding to the constant domain (Cϵ3) of free human IgE in the blood and interstitial fluid. Although efficacious, use of omalizumab is limited due to restrictions on patient weight and pre‐existing IgE levels, and frequent dosing (q2–4 weeks). A vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The first monoclonal Ab (mAb) approved for allergic asthma, omalizumab, recognizes a linear epitope on the Cε3 loop within the IgE heavy chain and prevents IgE receptor activation. 25,26 P10 peptide synthesized with the murine homolog of omalizumab’s epitope (DHPDFPKPIV) 18,26 at its C-terminus exhibited an average DLS diameter of ~15 nm (Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first monoclonal Ab (mAb) approved for allergic asthma, omalizumab, recognizes a linear epitope on the Cε3 loop within the IgE heavy chain and prevents IgE receptor activation. 25,26 P10 peptide synthesized with the murine homolog of omalizumab’s epitope (DHPDFPKPIV) 18,26 at its C-terminus exhibited an average DLS diameter of ~15 nm (Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…A second therapeutic experiment targeted the mouse IgE heavy chain epitope analogous to omalizumab’s IgE-binding site. 18,25,26,32 Competition enzyme-linked immunosorbent assays (ELISAs) established that the Abs induced in mice specifically bound IgE with nanomolar avidity and reduced the concentrations of circulating free IgE. Moreover, this same Ab response effectively suppressed an IgE-mediated anaphylactic response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human IgE-Fc has been shown to cross react with cynomolgus monkey effector cells (Saul et al, 2014), and the binding of human IgE to cynomolgus lung tissue potentially drives IgEmediated histamine release (Ishizaka et al, 1970;Wichmann et al, 2016). Later approved anti-IgE omalizumab showed binding to cynomolgus IgE (Fox et al, 1996;Meng et al, 1996), and efficacy assessment of a human-specific anti-IgE vaccine showed a reduction of circulating IgE, indicating the general suitability to test anti-IgE therapeutics in nonhuman primates (Weeratna et al, 2016). However, preclinical safety assessment of omalizumab in nonhuman primates revealed an age-dependent reduction of platelets, which was not detected in human patients, limiting the general transferability of data obtained in nonhuman primates (EMA, 2009a;Martin and Bugelski, 2012).…”
Section: Past and Future Approaches For Novel Respiratory Therapeuticmentioning
confidence: 99%